A multi-control vehicle-to-grid charger with bi-directional active and reactive power capabilities for power grid support - Tan K.M.; Padmanaban S.; Yong J.Y.; Ramachandaramurthy V.K. (Elsevier Ltd, 2023)
Charging (batteries); DC-DC converters; Electric inverters; Electric power transmission networks; Electric vehicles; Power control; Reactive power; Rectifying circuits; Vehicle-to-grid; Vehicles; Voltage control; Voltage regulators; Active and Reactive Power; Efficient control; Grid voltage controls; Power conversion; Power factor corrections; Reactive power compensation; Selection algorithm; Unity power factor; Electric power system control; accuracy assessment; algorithm; control system; electric vehicle; energy efficiency; operations technology; performance assessment; power generation; scenario analysis